Information services for small firms : a strategic channel or just noise - Gustavsson, Bengt Åke; Persson, Olle; Höglund, Lars (DFI-publikationer, ISSN 0349-9324, 1986)
Abstract (s. 11-12).
Keywords: informaatio; tietopalvelu; yritykset